Energy and Thermal Conductivity Assessment of Dimethyl-Ether and its Azeotropic Mixtures as Alternative Low Global Warming Potential Refrigerants in a Refrigeration System - Bolaji Bukola Olalekan (Sciendo, 2021)
Substituting Hydrofluorocarbons with natural refrigerants in domestic refrigerators will significantly reduce the direct contributions of fluorinated gases to global warming which will be of great environmental benefit. In this study, the performances of dimethyl-ether (RE170) and its azeotropic mixtures (R510A and R511A) in a refrigeration system were assessed theoretically and compare with that of conventional refrigerant. The study revealed that the three investigated alternative refrigerants exhibited significantly good heat transfer characteristics, low pressure ratio, high latent heat in the liquid phase which resulted in their high thermal conductivity and Volumetric Cooling Capacity (VCC). The thermal conductivity of the refrigerants reduces while the evaporating temperature rises and the value obtained for RE170 was the highest among the four refrigerants studied. The Coefficient of Performance (COP) for RE170, R510A and R511A were higher than that of R134a by 6.20, 10.06 and 3.02 % respectively while their power consumptions per ton of refrigeration were lower than that of R134a by 6.99, 11.04 and 1.47 % respectively. In conclusion, dimethyl-ether and its azeotropic mixtures performed better than R134a in that they have higher thermal conductivity, refrigerating effect, VCC, COP, lower power consumption per ton of refrigeration and hence, they can be considered as suitable replacements for R134a in domestic refrigerator.